Structural Collaboration Process, Staff and Non-Civil Servant in Job Seeker Card Service (AK-1) - Muhamad Taufik; Iqbal Miftakhul Mujtahid; Rino Ardhian Nugroho (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This study aims at investigateingthe strategy taken by the Department of Manpower and Industry of the city of Tarakan in overcoming the job seeker card service (AK-1). The problem was focused on collaboration between structural officials, staff, and non civil servant. To solve this problem, the theoretical references of Chris Ansell and Alisson Gash were used. The data were collected through interviews, observation and documentation and analyzed qualitatively. This study concludes that the collaboration process between structural officials, staff and non civil servant at the Department of Manpower and Industry of the city of Tarakan was going well, the strategy for making job seeker cards were able be applied. The service supporting factor was the existence of Information Technology (IT)-based applications, an inhibiting factor from services due to the Covid-19 pandemic. Services are still carried out based on health procedures set by the government.